Penguatan Pedagogi Reflektif Berbasis Komunitas: Transformasi Kompetensi Guru Pendidikan Jasmani di Wilayah Kepulauan Banda, Maluku Tengah - Anaktototy, Jacob; Souisa, Mieke (Jurnal Pengabdian Arumbai, 2026)
This community engagement program aims to enhance the pedagogical competence of primary school physical education teachers in Banda District through a community-based reflective approach. The initiative was designed to bridge the gap between reflective educational theory and teaching practices in island regions with limited resources. The methods included training workshops, participatory observation, and collaborative reflection involving 24 teachers from five primary schools. The findings indicate a significant improvement in teachers’ abilities to design contextual learning, manage student participation, and foster cross-institutional collaboration between schools, communities, and local cultural institutions. The Banda Reflective Pedagogical Model (BRPM) developed in this program successfully integrates local cultural values, ecological awareness, and adaptive pedagogical practices. This project provides conceptual contributions to the development of sustainable education and extends the understanding of reflective teaching within island-based educational contexts.